Wakaf Saham Sebagai Pengembangan Wakaf Produktif Dari Paradigma Fikih Klasik Menuju Paradigma Fikih Modern - Muhamad Saechu (CV. Kalimasada Group, 2025)
This article aims to provide an explanation of waqf in general and stock waqf in particular. The research method used is descriptive qualitative method with a literature study type. The results of this study are waqf is an important instrument in order to improve the welfare of Muslims. One of the waqfs of movable objects other than money is stock waqf. Stock waqf has its own special requirements and rules, different from waqf of immovable objects such as land. Stock waqf has a complete legal umbrella from the Law, Government Regulations, Regulations of the Minister of Religion and MUI Fatwas.